2013
DOI: 10.1364/ol.38.005401
|View full text |Cite
|
Sign up to set email alerts
|

Measuring mechanical strain and twist using helical photonic crystal fiber

Abstract: Solid-core photonic crystal fiber (PCF) with a permanent helical twist exhibits dips in its transmission spectrum at certain wavelengths. These are associated with the formation of orbital angular momentum states in the cladding. Here we investigate the tuning of these states with mechanical torque and axial tension. The dip wavelengths are found to scale linearly with both axial strain and mechanical twist rate. Analysis shows that the tension-induced shift in resonance wavelength is determined both by the ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(46 citation statements)
references
References 23 publications
2
41
1
2
Order By: Relevance
“…Another, rather more special example of a core-cladding interference twist/torsion sensor was presented in [78], where a continuously twisted solid-core PCF was used as a sensing element (the fiber was pre-twisted permanently by localized heating using a CO 2 laser). Continuously twisted solid-core PCF supports angular momentum states in the micro-structured cladding and these states couple to the core mode, giving rise to a series of resonance dips in the transmission spectrum, which respond to fiber twist/rotation, due to the modulation of the cladding states indexes.…”
Section: Sensor Based On Modulation Of Radial Shear Stress Distribmentioning
confidence: 99%
“…Another, rather more special example of a core-cladding interference twist/torsion sensor was presented in [78], where a continuously twisted solid-core PCF was used as a sensing element (the fiber was pre-twisted permanently by localized heating using a CO 2 laser). Continuously twisted solid-core PCF supports angular momentum states in the micro-structured cladding and these states couple to the core mode, giving rise to a series of resonance dips in the transmission spectrum, which respond to fiber twist/rotation, due to the modulation of the cladding states indexes.…”
Section: Sensor Based On Modulation Of Radial Shear Stress Distribmentioning
confidence: 99%
“…The transmission spectrum of such a structure exhibits a single and narrow notch whose position changes with strain or temperature [56]. Another example is a twisted PCF [57,58]. The twisting of the PCF is carried out while it is being heated.…”
Section: Point Sensors Based On Pcfsmentioning
confidence: 99%
“…In this way the twisting of the PCF is permanent. The transmission spectrum of a twisted PCF exhibits also a dip whose position changes with axial strain or temperature [57,58]. More recently, it was demonstrated that a photonic band gap PCF with an optically-trapped particle inside the hollow core can be used as a reconfigurable sensor [59].…”
Section: Point Sensors Based On Pcfsmentioning
confidence: 99%
“…The "space-filling" mode (SM) in the cladding forms an orbital angular momentum, which results in the tunable refractive index vector of the SM mode along the helical path [16].…”
Section: Introductionmentioning
confidence: 99%